Entrepreneurship and Employability Among Nigerian Graduates - Nwaoga, Chinyere T; Omeke, Faith C. (Richtmann Publishing, 2012)
Over 80% of graduates in Nigeria are unemployed, in spite of their qualifications, they are employable yetthey are not employed. The inability of the higher educational institutions to meet the needs of thesegraduates as well as promotion of economic self reliance and self sufficiency has resulted into youthsjoblessness (unemployment). These have added to increase in restiveness among Nigerian youths. Thisresearch is therefore undergone to investigate the relationship between entrepreneurship and employabilityamong Nigerian graduates. The paper, discussed the concept of entrepreneurship and employability. Sinceemployability is the act of having qualification that enables someone to employ you, the research alsolooked at the basic skills that can make one employable and at the same time becoming self reliant. Alsodiscussed are ways forward in promoting entrepreneurship among Nigerian youths and how teaching ofcreativity and problem solving skills can help reposition Nigerian graduates.